Analyzing Students' Understanding of the Concepts of Congruence and Resemblance through the Design of Folklore HLTs - Maftuhah, Maftuhah; Putra, Eric Dwi; Hidayatin, Nur (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study aims to analyze students' understanding of the concept of congruence and congruence through the design of Hypothetical Learning Trajectory (HLT) based on folklore. The research subjects were students of grade VIII at Ahlul Irfan Junior High School. Data were collected through observation, interviews, comprehension tests, and documentation during the learning process. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results showed that students with high ability were able to meet all indicators of understanding, such as restating concepts, categorizing objects, giving examples and non- examples, using various mathematical representations, choosing the right procedures, and applying concepts in problem solving. In contrast, students with low ability were only able to fulfill two indicators, namely restating concepts and categorizing objects based on certain characteristics, while they were not able to use representations, procedures, and logical reasoning in problem solving. This study reinforces the importance of using local cultural contexts in mathematics learning to address misconceptions and increase student engagement. Teachers are recommended to use folklore-based HLT as a contextual and interesting learning media, with special attention to assisting low ability students.